Analisis Pengaruh Jumlah Uang Beredar, Suku Bunga, dan Nilai Tukar terhadap Inflasi di Indonesia - Fauziyah; Ima Amaliah (UNISBA Press, 2024)
Abstract. This research aims to analyze the influence of the money supply, interest rates and exchange rates on inflation in Indonesia. Inflation is one of the main economic indicators that affects people's purchasing power and the country's economic stability. The variables studied—money supply, interest rates, and exchange rates are important factors in influencing the inflation rate. This research uses secondary data obtained from the Central Statistics Agency (BPS) and Bank Indonesia (BI) over the last 10 year period. The analytical method used is multiple regression to identify the relationship between the independent variables (money supply, interest rates, exchange rates) and the dependent variable (inflation). The results of the analysis show that the money supply has a significant positive influence on inflation, where an increase in the money supply tends to encourage an increase in the prices of goods and services. On the other hand, interest rates show a significant negative influence on inflation; An increase in interest rates can reduce inflation by reducing the amount of money in circulation. The exchange rate also has a significant effect on inflation, where depreciation of the rupiah exchange rate can increase import prices and contribute to domestic inflation. This research suggests the need for careful monetary policy to control the money supply and regulate interest rates so that inflation remains stable. Apart from that, effective exchange rate management is also important to maintain economic stability. Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh jumlah uang beredar, suku bunga, dan nilai tukar terhadap inflasi di Indonesia. Inflasi adalah salah satu indikator ekonomi utama yang mempengaruhi daya beli masyarakat dan stabilitas ekonomi negara. Variabel-variabel yang diteliti—jumlah uang beredar, suku bunga, dan nilai tukar merupakan faktor penting dalam mempengaruhi tingkat inflasi. Penelitian ini menggunakan data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) dan Bank Indonesia (BI) selama periode 10 tahun terakhir. Metode analisis yang digunakan adalah regresi berganda untuk mengidentifikasi hubungan antara variabel independen (jumlah uang beredar, suku bunga, nilai tukar) dan variabel dependen (inflasi). Hasil analisis menunjukkan bahwa jumlah uang beredar memiliki pengaruh positif yang signifikan terhadap inflasi, dimana peningkatan jumlah uang beredar cenderung mendorong kenaikan harga-harga barang dan jasa. Sebaliknya, suku bunga menunjukkan pengaruh negatif yang signifikan terhadap inflasi; kenaikan suku bunga dapat menurunkan inflasi dengan mengurangi jumlah uang yang beredar. Nilai tukar juga berpengaruh signifikan terhadap inflasi, di mana depresiasi nilai tukar rupiah dapat meningkatkan harga impor dan berkontribusi pada inflasi domestik. Penelitian ini menyarankan perlunya kebijakan moneter yang hati-hati untuk mengendalikan jumlah uang beredar dan mengatur suku bunga agar inflasi tetap stabil. Selain itu, pengelolaan nilai tukar yang efektif juga penting untuk menjaga kestabilan ekonomi.